IMPROVING SCIENTIFIC LITERACY SKILLS INTEGRATED WITH THE PROBLEM-BASED LEARNING MODEL - Idris, Irfandi; Maryam, Andi; Rusni, Rusni; Rakhmiyanti, Rakhmiyanti; Ahmad, Rizky Ekawati (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to improve elementary school students’ scientific literacy skills through the implementation of the Problem Based Learning (PBL) model. The research subjects were 28 fifth-grade students at SDN 26 Kota Sorong. The method used was classroom action research conducted in two cycles. Instruments included scientific literacy tests, observation sheets, and interviews. The results showed that the average scientific literacy score increased from 55.6 in the pretest to 79.2 in the posttest, with a total improvement of 42.4%. Improvements occurred across all aspects of scientific literacy, including explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting data and evidence scientifically. The PBL model was proven to encourage active student engagement, foster critical thinking skills, and make the learning process more meaningful. Therefore, PBL is recommended as an effective instructional approach to enhance scientific literacy in elementary school science learning.Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan literasi sains siswa sekolah dasar melalui penerapan model pembelajaran Problem Based Learning (PBL). Subjek penelitian adalah siswa kelas V SDN 26 Kota Sorong yang berjumlah 28 orang. Metode yang digunakan adalah penelitian tindakan kelas dengan dua siklus. Instrumen yang digunakan meliputi tes literasi sains, lembar observasi, dan wawancara. Hasil penelitian menunjukkan bahwa rata-rata kemampuan literasi sains siswa meningkat dari 55,6 pada pretest menjadi 79,2 pada posttest, dengan peningkatan sebesar 42,4%. Peningkatan terjadi pada seluruh aspek literasi sains, yaitu menjelaskan fenomena secara ilmiah, mendesain dan mengevaluasi penyelidikan ilmiah, serta menafsirkan data dan bukti secara ilmiah. Model PBL terbukti mendorong keterlibatan aktif siswa, mengembangkan kemampuan berpikir kritis, dan menjadikan proses pembelajaran lebih bermakna. Oleh karena itu, model PBL direkomendasikan sebagai pendekatan pembelajaran yang efektif dalam meningkatkan literasi sains di sekolah dasar